2007
DOI: 10.1097/dmp.0b013e31814cfa54
|View full text |Cite
|
Sign up to set email alerts
|

Is Overtriage Associated With Increased Mortality? Insights From a Simulation Model of Mass Casualty Trauma Care

Abstract: Increasing overtriage may have positive, negative, or mixed effects on critical mortality in this trauma system simulation model. These results, which contrast with prior analyses describing a positive linear relationship between overtriage and mortality, highlight the need for alternative metrics to describe trauma system response after MCIs. We explore using the relative number of critical patients to available and staffed treatment units, or the critical surge to capability ratio, which exhibits a consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Under certain circumstances, it has been suggested that overtriage may also lead to increased mortality among critically injured patients. [14][15][16] As health care providers look for cost savings, this study provides additional support for using Field Triage guidelines to reduce overtriage (cost savings of $7,264 per patient at a 40% overtriage rate).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under certain circumstances, it has been suggested that overtriage may also lead to increased mortality among critically injured patients. [14][15][16] As health care providers look for cost savings, this study provides additional support for using Field Triage guidelines to reduce overtriage (cost savings of $7,264 per patient at a 40% overtriage rate).…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Excessive overtriage has been associated with additional mortality among severely injured patients. [14][15][16] Because trauma centers exist within large and complex medical systems, the causes of overtriage are often complex and interrelated. Crowding in EDs can result in an overflow of patients that can adversely impact trauma center functioning.…”
mentioning
confidence: 99%
“…27 Examples of disaster response-based metrics that are currently being studied include appropriateness of triage level, transportation to a hospital with suitable treatment capability, and time-dependent mortality of victims. [28][29][30] Development of metrics and measurable objectives for disaster response allows EMS leadership to quantify response effectiveness and reproduce best practices.…”
Section: Development Of Performance Metricsmentioning
confidence: 99%
“…The impact of over-triage on mortality is less clear but may impact overall survival. [5][6][7] The magnitude of this mistriage threat remains unknown to the large number of communities in the U.S. that utilize START for disaster triage. In addition, no data exist demonstrating that START triage influences decisions regarding which patients should be transported to hospitals first.…”
Section: Importancementioning
confidence: 99%